Tuning impact in Latin America: is there implementation beyond design? - Pablo Beneitone; Maria Yarosh (Universidad de Deusto, 2015)
Deusto International Tuning Academy is undertaking a large-scale study to analyse the impact Tuning projects may have had in participating universities. More particularly, the study hopes to provide an unambiguous answer regarding the presence or absence of the implementation of a competence-based student-centred approach in the different world regions where Tuning projects have taken place. The present article focuses only on Latin America where two Tuning projects have been developed. It describes the findings of the first two stages of the study. After reporting the data, the authors argue that there is evidence of a Tuning impact in each of three intended impact domains: (1) understanding of the importance of a shift from content- to competence-based education; (2) provision of institutional support necessary to facilitate this change; and (3) appropriate teaching, learning and assessment within the general framework of the study plans and degree profiles.